SUPPLY AND DEMAND SIDE DRIVERS OF REGIONAL ECONOMIC GROWTH: EVIDENCE FROM JAVA ISLAND - Tania Zahra Zhafira; Aris Soelistyo; Muhammad Firmansyah (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to analyze the influence of supply-side and demand-side factors on economic growth in six provinces on Java Island during the 2015–2024 period. Supply-side factors include mean years of schooling, life expectancy, labor productivity, and the number of employed labor force, while the demand-side factor is represented by government consumption expenditure. Economic growth is measured using Gross Regional Domestic Product (GRDP) at constant prices. This study employs a quantitative approach using panel data regression with 60 observations, and the best estimation model is selected through the Chow test and Hausman test. The results show that all independent variables simultaneously have a significant effect on economic growth in Java. Partially, supply-side variables have a more dominant influence than government expenditure. These findings indicate that improvements in human capital quality and labor productivity play an important role in promoting regional economic growth. This study is limited by its coverage, which only includes six provinces on Java Island, and by the limited number of variables used, so it may not fully capture all determinants of economic growth. Therefore, future research is recommended to incorporate additional variables such as investment, infrastructure, and technology, expand the regional scope, and use a longer observation period or different analytical methods to produce more comprehensive results with stronger generalizability.